YOUR BLOOD PRESSURE IS 90/60 mmHg: AN ENGLISH FOR NURSING WORKSHOP FOR NURSES IN TANGERANG REGENCY - Komilie Situmorang; Santa Maya Pramusita; Magda Fiske Rumambi; Maria Maxmilla Yoche Arkianti; Riama Marlyn Sihombing (Bajang Institute, 2025)
Nurses play an important role in the recovery of patients through nursing care and therapeutic communication. They must care for all patients regardless of differences in ethnicity, religion, or language. Therefore, it is important for nurses to be able to communicate in English. This community service aims to provide English language support for nurses. Through the provision of modules and onsite classes, nurses were given workshops and practiced nursing care in English. The results showed an increase in vocabulary and confidence in the nurses. At the end of the community service, nurses are also equipped with basic daily skills in providing nursing care in English.